KENNEDY AND SOEKARNO IN POPULAR MOVIES: A TRANSNATIONAL PERSPECTIVE - Mala Hernawati (Rubikon : Journal of Transnational American Studies, 2015)
A leader is someone who is perceived to represent a community. In nations that apply democracy, where people can choose their president through general election, the chosen leader is certainly someone who can meet the majority’s taste and criteria. President Kennedy from the United States and President Sukarno from Indonesia are two examples of the popular leaders that have been adored by their people through generations. This research examines leadership representation of Kennedy and Sukarno in movies, how their characters are built on screen, and the significance of their appearance in movies. This research employs Representation Theory from Stuart Hall combined with Transnational Theory of New American Studies. This research is able to explain the connection between popular fiction and the social and political phenomena in both countries, the US and Indonesia, in the time before the general election. Besides, this research finds shared values and ideology in Kennedy’s and Sukarno’s leadership represented in movies. Keywords: leadership, movies, representation, ideology, transnational